Simulation of Hybrid Series Active Filter for Household Application: Enhancing power quality in residential households using a hybrid series active filter (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper a Multilevel Transformer less Hybrid Series Active Filter (Multilevel-THSeAF) is proposed to enhance the power quality of a single-phase residential household. The proposed topology reflects new trends of consumers towards electronic polluting loads and integration of renewable sources which in fact may lead to the scope of a reliable and sustainable supply. This paper contributes to improvement of power quality for a modern single-phase system and emphasis integration of a compensator with energy storage capacity to ensure a sustainable supply. A proportional resonant (PR) regulator is implemented in the controller to prevent current harmonic distortions of various non-linear loads to flow into the utility. The main significant features of the proposed topology include the great capability to correct the power factor as well as cleaning the grid simultaneously, while protecting consumers from voltage disturbances, sags, and swells during a grid perturbation. It investigates aspects of harmonic compensation and assesses the influence of the controller’s choice and time delay during a real-time implementation. Combinations of analysis and experimental results performed on a laboratory setup are presented for validation.